Rothe approach to the existence of solution of an ablation-transpiration cooling control system. (1993) - Zhu, Guo Bao
Abstract : A one dimensional ablation model with transpiration cooling control and nonlinear effect is studied, which is a distributed parameter control system with moving boundary and both governing equation and boundary conditions involving control variable. A solution is given by a Rothe approximation scheme.